Temporal development of the correlation between ozone and potential vorticity in the Arctic in the winters of 1988/1989, 1989/1990, and 1990/1991 - Rummukainen, Markku; Knudsen, Bjorn; Jorgensen, Torben S.; Neuber, Roland; Braathen, Geir O.; Kyro, Esko; Vondergathen, Peter; Fabian, Rolf (1994)
Ozone sonde data of the winters 1988/89, 1989/90, and 1990/91 from a group of Arctic stations are used in this study. The ozone mixing ratio on several isentropic surfaces is correlated to the potential vorticity (P). The P is based on the initialized analysis data from the European Center for Medium-Range Weather Forecasts. Similar investigations were made by Lait et al. (Geophys. Res. Lett., 17, 521-524, March Supplement 1990) for the AASE campaign (January and February 1989), showing how the ozone mixing ratio varies with the distance to the edge of the vortex. Their findings are confirmed and extended to the following two winters. Furthermore we have studied the temporal development of the P-ozone correlations during these winters in order to recognize any chemical ozone depletion.